Stem Cells Applications in Regenerative Medicine and Disease Therapeutics. (19th July 2016) - Mahla, Ranjeet Singh
Abstract : Regenerative medicine, the most recent and emerging branch of medical science, deals with functional restoration of tissues or organs for the patient suffering from severe injuries or chronic disease. The spectacular progress in the field of stem cell research has laid the foundation for cell based therapies of disease which cannot be cured by conventional medicines. The indefinite self-renewal and potential to differentiate into other types of cells represent stem cells as frontiers of regenerative medicine. The transdifferentiating potential of stem cells varies with source and according to that regenerative applications also change. Advancements in gene editing and tissue engineering technology have endorsed the ex vivo remodelling of stem cells grown into 3D organoids and tissue structures for personalized applications. This review outlines the most recent advancement in transplantation and tissue engineering technologies of ESCs, TSPSCs, MSCs, UCSCs, BMSCs, and iPSCs in regenerative medicine. Additionally, this review also discusses stem cells regenerative application in wildlife conservation.